Women Times Three: Writers, Detectives, Readers - Klein, Kathleen Gregory (Bowling Green State University Popular Press, 1995)
This volume explores the range of relationships among women writers, women detectives and women-centered mystery fiction, and women readers. Focusing on writers as diverse as Sara Paretsky, Joan Hess, Sarah Caudwell, P.D. James, Katherine V. Forrest, Mary Roberts Rinehart, Sue Grafton, D.R. Meredith, Dorothy L. Sayers, and Barbara Wilson, the authors analyze the development of detective fiction with a different agenda: the woman-authored woman detective. Examined through the eyes of actual and hypothetical women readers of the genre, these eleven essays concentrate new attention on the trio of reader, writer, and text when all three are modified by the terms "woman" and "mystery." The first essay collection to propose this gender and genre specific analysis, Women Times Three offers its readers a careful theoretical and critical investigation of both historical and contemporary models of consistently "new" mystery fiction., The essays' authors are not only widely published scholar-critics of mystery/detective fiction but also dedicated fans of the genre. Familiar with the full scope of mystery fiction, they bring insight and enthusiasm to their writing.
Keywords: 20th century; Women; Books and reading; Detective and mystery stories, American; English-speaking countries; English-speaking countries; Authors and readers; English-speaking countries; Feminism and literature; History; History and criticism; American fiction; History and criticism; Detective and mystery stories, English; History and criticism; English fiction; History and criticism; Women detectives in literature; Women and literature; Women authors; dept.eng; faculty_collection